Setting a human rights agenda for archivists in Cape Town, 2003: a personal reminiscence. Issue 1 (1st December 2022) - Dominy, Graham
Abstract : The 2003 CITRA conference on "Archives and Human Rights" held in Cape Town, South Africa was a watershed for the ICA. For the first time the issue of archives and human rights moved firmly on to the international body's agenda. It must not be forgotten that Charles Kecskeméti was one of the pioneers promoting the recognition of this issue. This article is a personal reminiscence of the trials and triumphs in organizing the conference. From the South African perspective, two factors contributed to the success of the conference. The first was the important keynote address by Nobel Peace Laureate Archbishop Emeritus Desmond Tutu, and the second was the meeting of ministers responsible for archives in southern and eastern Africa and the declaration on archives that they adopted. The article also mentions some of the more amusing and challenging moments around the conference.